2013
DOI: 10.1214/ejp.v18-2118
|View full text |Cite
|
Sign up to set email alerts
|

A phase transition for the limiting spectral density of random matrices

Abstract: We analyze the spectral distribution of symmetric random matrices with correlated entries. While we assume that the diagonals of these random matrices are stochastically independent, the elements of the diagonals are taken to be correlated. Depending on the strength of correlation the limiting spectral distribution is either the famous semicircle law or some other law, related to that derived for Toeplitz matrices by Bryc, Dembo and Jiang (2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…We begin the proof with large deviations estimates that demonstrate the efficiency of the indicators X N,± defined in (8). They are immediate consequences of Hoeffding's inequality.…”
Section: Proof Of the Main Resultsmentioning
confidence: 91%
“…We begin the proof with large deviations estimates that demonstrate the efficiency of the indicators X N,± defined in (8). They are immediate consequences of Hoeffding's inequality.…”
Section: Proof Of the Main Resultsmentioning
confidence: 91%
“…2. The proof in [19] uses the moment method. It allows the authors to give an expression for the moments of σ β in terms of m(β) (see (43)).…”
Section: Remarks 75mentioning
confidence: 99%
“…Similar attempts have been made in Schenker and Schulz-Baldes (2005), where a limited number of correlated entries are admitted, Götze and Tikhomirov (2006), where a martingale structure of the entries is imposed, Friesen and Löwe (2013b), where the diagonals of the (symmetric) matrices were filled with independent Markov chains or in Löwe and Schubert (2016), where the upper triangular part of the matrix is filled with a one-dimensional Markov chain. On the other hand, Friesen and Löwe (2013a) and Hochstättler et al (2016) study matrices where either the diagonals or the entire matrix is built of exchangeable random variables. In particular, in Friesen and Löwe (2013a) it was shown that there is a phase transition: If the correlation of the exchangeable random variables go to 0, the limit of the ESD is the semi-circle law, while otherwise it can be described in terms of a free convolution of the semi-circle law with a limiting law obtained in Bryc et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Friesen and Löwe (2013a) and Hochstättler et al (2016) study matrices where either the diagonals or the entire matrix is built of exchangeable random variables. In particular, in Friesen and Löwe (2013a) it was shown that there is a phase transition: If the correlation of the exchangeable random variables go to 0, the limit of the ESD is the semi-circle law, while otherwise it can be described in terms of a free convolution of the semi-circle law with a limiting law obtained in Bryc et al (2006). In this note we will answer a question by C. Deninger (private communication) and extend the results from Friesen and Löwe (2013a) and Friesen and Löwe (2013b) to ergodic sequences of random variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation